A New Dynamical Parameter for the Study of Sticky Orbits in a 3D Galactic Model - Zotos Euaggelos E. (Open Astronomy, 2011)
A 3D dynamical model is used to study the motion in the central parts of an elliptical galaxy, hosting a massive and dense nucleus. Our aim is to investigate the regular or chaotic character of the motion, with emphasis in the different chaotic components, as well as the sticky regions of the dynamical system. In order to define the character of the motion in the 2D system, we use the classical method of the Poincaré x − px phase plane, the Lyapunov Characteristic Exponent (LCE) and the dynamical parameter - the S(c) spectrum. Then the results obtained from the 2D system are used to investigate the properties of the 3D system. For this, we introduce and use a new dynamical parameter, the S(k) spectrum, which proves to be a very reliable and fast method to detect the islandic motion and the evolution of the sticky orbits in the 3D system. Numerical experiments conducted by the new S(k) spectrum suggest that the different chaotic components in the 3D system do not interact for time intervals much larger than the age of the galaxy. The results indicate that the different sticky regions do not lead to a unified chaotic sea. Thus, the behavior of the 3D sticky orbits differs from that observed in the 2D system. Furthermore, the 3D motion near the center of a triaxial elliptical galaxy seems to be very complicated, displaying several families of resonant orbits, different chaotic components and sticky regions, while only a small fraction of orbits is regular. The comparison with earlier results reveals the importance of the conception of the new dynamical spectrum.